Penerapan Teknik Pengambilan Gambar oleh Director of Photography dalam Produksi Karya Video Feature: “Suara dari Unpad: Jejak Calung Jinjing” (International Forum of Researchers and Lecturers, 2025)
This study aims to analyze the process of creating an audiovisual feature that explores the commodification of calung jinjing as a cultural medium that has undergone a functional shift from communication to entertainment. The research employs a descriptive qualitative method using a practice-based research approach, in which the process of audiovisual creation serves as the primary method of inquiry. The author is directly involved as the Director of Photography throughout all stages of production, including pre-production, production, and post-production. The results indicate that the application of cinematographic elements—such as visual composition, lighting, camera movement, and lens selection—plays a significant role in strengthening the historical and cultural meanings of calung jinjing. These visual strategies effectively support the narrative in conveying the process of cultural commodification in a communicative and aesthetic manner. The study demonstrates that audiovisual feature production can function not only as a form of cultural documentation but also as an academic medium for interpreting and preserving local cultural values through visual storytelling.